Heterotraining and Auto-training as Methods of Psychological Preparation - Sergey Georgievich Gagonin (Управленческое консультирование, 2018)
Self-control as independent, without assistance management of the person by itself is one of his major characteristics providing high achievements. Considering extent of development of self-regulatory mechanisms and the clearness of orientation of the person to their continuous improvement, it is possible with sufficient degree of probability to predict progress of the personality in various fields of activity.